Causality Between Tourism Industry Development and the Ecological Sustainability In Marine Environment: A Convergence and Divergence among Stakeholder With Mactor Analysis - Mafruhah, Izza; Supriyono, Supriyono; Mulyani, Nunung Sri; Istiqomah, Nurul (International Journal of Energy Economics and Policy, 2020)
Tourism is currently one of the mainstay sectors in increasing income in virtually all countries in the world. In the past decade, the tourism sector has contributed significantly to the income of countries in the Southeast Asia region. The growth of the tourism sector reached 8.3%, well above global growth of only 3.6%. Indonesia is one country with vast tourism potential. However, it is feared that the massive growth and potential will have an impact on the degradation of environmental quality, especially marine, which constitutes two-thirds of Indonesia’s total area. This study aims to explore the profile of ecology and marine based tourism in Central Java Province, to analyze the supporting factors priority in the development of natural and marine tourism based on community empowerment, and to analyze stakeholders’ participation in tourism development. The research used sequential mix method with Geographic Information System, ATLAS.ti, and stakeholder analysis with MACTOR as analysis tools. This study found that environmental and marine tourism development requires infrastructure and facilities, institutional preparation, and community empowerment. Ecomarine tourism development requires the involvement of various parties including regulators, executors, supporting institutions, targets, and the community as the main actor. The development model of ecomarine tourism is based on the concept of who does what, where the people gains empowerment support through community capacity building, transformation of work from fishermen/farmers to tourism business operators, local assistance, and the opening of tourism networks. Keywords: Ecomarine, tourism development, stakeholder, MACTOR, convergence JEL Classifications: Q56, Q57 DOI: https://doi.org/10.32479/ijeep.7989